The chemical biology of ubiquitin - Burslem, George M. (Biochimica et biophysica acta. General subjects, 2022)
This mini-review will cover the various chemical biology approaches employed to prepare and modulate ubiquitin chains and the ubiquitin-proteasome system. Emphasis will be given to the biochemistry and chemical biology of poly-ubiquitin chain preparation as a tool to elucidate its roles in biological systems as well as the hijacking of the ubiquitin proteasome system using heterobifunctional compounds to induce intracellular ubiquitination. •Ubiquitination is a diverse and critical to understand post-translational modification.•Chemical biology approaches provide unique opportunities to prepare and study polyubiquitin chains.•Novel tools are emerging for the control of ubiquitination inside mammalian cells.